2017
DOI: 10.1248/bpb.b16-01025
|View full text |Cite
|
Sign up to set email alerts
|

Histone Deacetylase Inhibitors Sensitize Murine B16F10 Melanoma Cells to Carbon Ion Irradiation by Inducing G1 Phase Arrest

Abstract: and were then exposed to two types of radiation (carbon ions and gamma-rays). We found that HDACis enhanced the radiation-induced apoptosis and suppression of clonogenicity that was induced by irradiation, having a greater effect with carbon ion irradiation than with gamma-rays. Carbon ion irradiation and the HDACi treatment induced G2/M and G0/G1 cell cycle arrest, respectively. Thus, it is considered that HDACi treatment enhanced the killing effects of carbon ion irradiation against melanoma cells by inducin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…SAHA is an anti-tumor drug and it is known that the cytotoxic effects are limited to transformed and cancerous cells [ 31 ]. Many reports showed SAHA induced radio-sensitization in cancer cells with photon and hadron radiation [ 17 , 18 , 19 , 20 , 32 ]. A prior study showed SAHA’s selective radiosensitization to cancer cells (sarcoma, glioblastoma, squamous cell carcinoma) with photon irradiation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SAHA is an anti-tumor drug and it is known that the cytotoxic effects are limited to transformed and cancerous cells [ 31 ]. Many reports showed SAHA induced radio-sensitization in cancer cells with photon and hadron radiation [ 17 , 18 , 19 , 20 , 32 ]. A prior study showed SAHA’s selective radiosensitization to cancer cells (sarcoma, glioblastoma, squamous cell carcinoma) with photon irradiation [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…These DNA repair inhibitory effects by HDACi were combined with photon ionizing radiation and chemotherapeutic agents, and showed synergistic effects for cell killing. However, a combination of HDACi with particle radiation, including proton and carbon ion, are still limited [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…In cancers that respond poorly to chemotherapy, treatment with HDACis can increase the sensitivity of the cancer cells to other drugs and treatments such as radiotherapy. Inhibitors of HDAC such as asvorinostat, depsipeptide, MS-275, valproic acid (VPA), and trichostatin A (TSA), show additive or synergistic anticancer activity when used along with conventional chemotherapeutic drugs [18,19,20]. Valproic acid selectively modulates the activity of histone deacetylase 2 (HDAC2) and induces proteasomal degradation [21].…”
Section: Introductionmentioning
confidence: 99%
“…Recent in vitro studies in cell lines have shown VPA to be a radiosensitizer in melanoma, breast cancer, osteosarcoma and colorectal cancer . Several in vivo and in vitro studies as well as clinical studies have also indicated that VPA has radiosensitizing effects for gliomas and is radioprotective to normal brain tissue .…”
Section: Resultsmentioning
confidence: 99%
“…123 However, in patients with advanced melanoma, the combination of VPA and chemoimmunotherapy did not result in outcomes that were clearly superior to standard therapy. 124 Recent in vitro studies in cell lines have shown VPA to be a radiosensitizer in melanoma, 125 breast cancer, 126 osteosarcoma 127 and colorectal cancer. 128 Several in vivo and in vitro studies as well as clinical studies have also indicated that VPA has radiosensitizing effects for gliomas and is radioprotective to normal brain tissue.…”
Section: Potential Use In Oncologymentioning
confidence: 99%